Evaluation of different treatments in control of Oligonychus afrasiaticus in date palm orchards of Iran - Masoud Arbabi; Masoud Latifian; Majied Askari; Mohammad Taghi Fasihi; Mohammad Reza Damghani; Nader Gholmohammad zadeh Khiaban,; Horieh Rezai (Persian Journal of Acarology)
Oligonychus afrasiaticus is a major pest of date palm orchards in Iran and Middle East countries. Effects of amitraz, fenpropathrin, fenpyroximate, fenazaquin, propargite), tetradifon, and hexythiazox were evaluated in southern part of Iran. The complete randomized block designed with three replications used on Mordarsang, Kabkab, Barhi, Mazafati, and Halileh major date varieties cultivated in Hormozgan, Bushehr, Khuzestan, Kerman and Sistan and Baluchistan provinces, respectively. Two small date clusters randomly were detached from each replicate and number of spider mite mobile stages were counted on epidermis of 20 date fruits at intervals one day before, 3, 7, 14 and 20 days after treatments. Mean mite densities before treatments found varied from 1.4–69 mites among treatments, provinces and year of studies. Mean mortality analysis variance was found significant (p > 0.01) in all factors. First and last sign of web span around date fruits cluster observed in Khuzestan, and Sistan and Baluchistan in April–May and July–August, respectively. High, medium and weak treatment mortality percentage during 3rd day sampling time in two years recorded for Hormozgan, Kerman, Khuzestan, Bushehr, and Sistan and Baluchistan provinces. Absolute mite pest control obtained at 20th day sampling time during 2nd year in Kerman and imperfection mortality in other places in two years. Date spider mite treated with tetradifon has a half century history in Iran and fenazaquin with low dose (0.3%), caused high mortality rate in most of provinces. Absolute mite controlled (100%) and prolongation effects recorded by water sprayed during 20th day sampling time in the 1st and 2nd year in Hormozgan and Kerman provinces, respectively.